Pemerolehan Bunyi Bahasa Anak Usia Prasekolah: Studi Kasus Pelafalan Vokal dan Konsonan - Siti Muntapiroh; Eka Sri Pratiwi; Sundawati Tisnasari (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study concludes that children's language acquisition is strongly influenced by their living environment. Children raised in families that engage in frequent conversation tend to develop better speaking skills. The research aimed to examine the phonological pronunciation of a 4-year-old child. The study was conducted in the Baros area on May 31, 2025, using a descriptive qualitative method over a single day. Data were collected through direct observation, daily notes, and interviews with the child's mother. The subject, Fajri, is the second son of Mina and Doni. Findings revealed that Fajri could pronounce vowels clearly but still struggled with certain consonants. For instance, he pronounced the letter [S] as 'tc'. This difficulty is likely due to the immaturity of his speech organs and unfamiliarity with certain sounds.